Synergistic Activity of Colistin in Combination With Resveratrol Against Colistin-Resistant Gram-Negative Pathogens - Antonio Cannatelli; Silvia Principato; Olga L. Colavecchio; Lucia Pallecchi; Gian Maria Rossolini; Gian Maria Rossolini (Frontiers in Microbiology, 2018)
Objectives: In this study, we investigated the antimicrobial activity of resveratrol in combination with colistin, a last-resort agent for the treatment of severe infections caused by multidrug resistant Gram-negative pathogens.Methods: The synergistic activity and the bactericidal activity of colistin in combination with resveratrol was investigated by checkerboard assays and time-kill assays, respectively. A total of 21 strains were investigated, including 16 strains of different species (Klebsiella pneumoniae, n = 6, Escherichia coli, n = 6; Citrobacter braakii, n = 1; Stenotrophomonas malthophilia, n = 1; Enterobacter cloaceae, n = 1; Acinetobacter baumannii, n = 1) with acquired colistin resistance, three colistin-susceptible K. pneumoniae precursors, and two strains of intrinsically colistin-resistant species (Serratia marcescens, n = 1; Proteus mirabilis, n = 1). Mechanisms of acquired colistin resistance included chromosomal mutations (i.e., mgrB, pmrAB) and plasmid genes (mcr-1, mcr-1.2).Results: Resveratrol did not show any significant intrinsic antimicrobial activity. Overall, a relevant synergistic antimicrobial activity of resveratrol in combination with colistin was observed with all tested strains, except for the three colistin-susceptible K. pneumoniae strains, and for two mcr-1-positive E. coli strains. In time-kill assays, performed with 15 selected strains, the combination of colistin 2 mg/L plus resveratrol 128 mg/L was bactericidal with 11 strains, and bacteriostatic for the remaining ones.Conclusions: Resveratrol was found to potentiate colistin activity against a wide panel of colistin-resistant strains, regardless of species and resistance mechanisms, which would deserve further investigation for potential clinical applications.